Development of systemic lupus erythematosus after dupilumab treatment in a case of atopic dermatitis. Issue 5 (27th February 2022) - Okune, Mari; Okiyama, Naoko; Fukuzono, Maki; Sasaki, Katsuhito; Nomura, Toshifumi
Abstract: Dupilumab, a monoclonal antibody that specifically inhibits signal transductions by interleukin (IL)‐4 and IL‐13, has been used to treat T‐helper (Th)2‐type allergic disorders, including atopic dermatitis and asthma. We report a 21‐year‐old female patient with atopic dermatitis who developed systemic lupus erythematosus (SLE) unexpectedly after dupilumab treatment. Her skin lesions partially improved after dupilumab treatment; however, a part of her skin lesions on the face, nape, and upper extremities were refractory even after a 15‐month period of dupilumab treatment. These dupilumab‐refractory skin lesions were histopathologically diagnosed as cutaneous lupus erythematosus, moreover, subsequent phenomenons, diffuse alopecia, joint pain, lymphopaenia, hypocomplementemia, and positivities for anti‐nuclear, anti‐double‐stranded DNA, anti‐U1 ribonucleoprotein, anti‐Smith, and anti‐Sjögren's syndrome‐related antigen A antibodies made a diagnosis of SLE. Our retrospective investigations on her serum samples indicted that these abnormalities of laboratory examinations had not appeared at the initiation of dupilumab treatment. Our case at least indicated that dupilumab was not effective in treating SLE. Moreover, inhibition of Th2‐type immune responses by dupilumab may accelerate the pathogenesis of Th1‐related inflammatory disorders, including SLE, as observed in our case. Our case also presented another possibility that dupilumab has no effect on the progression of underlying SLE. Because a significant relationship exists between atopic dermatitis/asthma and the risk of SLE, the utility of dupilumab should be carefully considered for each case.